(untitled) (Research, Society and Development, 2025)
Genetic diseases represent a heterogeneous group of health conditions with a significant impact on the global population. Many are individually rare, but collectively they have a relevant prevalence, in addition to high morbidity, often manifesting in childhood. In Brazil, despite the National Policy for Comprehensive Care for People with Rare Diseases (PNAIPDR) having been instituted to organize care for these conditions, the lack of local epidemiological data and specialized services remains a challenge. The present study aims to understand the profile of genetic diseases of patients treated at the Physiotherapy School Clinic of a University Center in Itabira, Minas Gerais, seeking to provide unprecedented local data for the region. This is a descriptive and retrospective study that analyzed 1,676 medical records of patients treated between January 2014 and June 2024. Forty-one medical records with genetic diagnoses were found. Genetic syndromes were more common (61%) than chromosomal syndromes (39%), with Duchenne Muscular Dystrophy, Cystic Fibrosis, Sickle Cell Anemia and West Syndrome standing out among the genetic syndromes, and Down Syndrome (88%) among the chromosomal syndromes. Three cases of consanguineous marriage were found. The study provides an initial overview of genetic diseases that require physiotherapy rehabilitation in the region, highlighting the need for greater attention to early diagnosis, multidisciplinary management and improvement of data collection in health services, serving as a subsidy for future surveillance and assistance actions in the city of Itabira.